Hubungan Pengetahuan dan Sikap Ibu dalam Pencegahan Penyakit Menular Seksual dengan Gonore di Desa Lau Lugur Kecamatan Salapian Kabupaten Langkat Tahun 2022 - Juli Evianna (JURNAL RISET RUMPUN ILMU KESEHATAN, 2022)
More than 1 million sexually transmitted diseases (STDs) occur every day. In one year there are an estimated 357 million new sexually transmitted infections (STIs) worldwide. Sexually Transmitted Diseases are a type of reproductive tract infection (ISR) that is transmitted through sexual contact. This writing aims to determine the relationship between mothers' knowledge and attitudes in preventing sexually transmitted diseases and gonorrhea in Lau Lugur Village, Salapian District, Langkat Regency in 2022. The independent variable is mothers' knowledge and attitudes in preventing sexually transmitted diseases and the dependent variable is Gonorrhea. The type of writing used is analytical observational with a cross sectional approach method. The population was 210 mothers and the sampling method used in this writing was Quota Sampling, taking the number of samples determined by the author, namely 33 mothers. The data used in this writing are primary data through questionnaires and checklists and secondary data obtained from the village head. The statistical test used is the chi-square statistical test α=0.000. The results of the analysis showed that of the 33 respondents there were 3 people (9.1%) who had good knowledge, 7 people (21.2%) who had sufficient knowledge. And 23 people (69.7%) had less knowledge. The chi-square statistical results showed that the knowledge value was p=0.000 and the attitude value was p=0.000< α=0.05, which means there is a relationship between mother's knowledge and attitude in preventing sexually transmitted diseases and gonorrhea. It is hoped that mothers in Lau Lugur Village, Salapian District, Regency Steps to increase knowledge about gonorrhea and attitudes towards preventing gonorrhea.